Pelvic-floor muscle strength in pilates practitioners/ Fuerza muscular del piso pélvico en los practicantes de pilates/ Força muscular do assoalho pélvico em praticantes de pilates - Latorre, Gustavo Fernando Sutter (2020)
Objective: to investigate the correlation between practicing Pilates and pelvic floor muscle strength. Method: cross-sectional study conducted with women that practiced the Pilates method for more than six months and sedentary women. Pelvic floor muscle strength was evaluated through the functional scale of the International Continence Society, betwen August and September 2017, in a clinic specialized in Pilates practice in the municipality of Poá, São Paulo, Brazil. Results: among the 41 women who participated in the study, 12 were Pilates practitioners. The Pilates group was, on average, ten years younger. The degrees of muscle strength of the pelvic floor in the Pilates group were higher than those in the control group (p = 0.0001). Conclusion: despite the small sample size and the age bias of the samples, it is possible that Pilates is in favor of a better pelvic floor function in women. One out of ten women is unable to contract the pelvic floor under verbal command, being part of a risk group for local dysfunctions in physical activities in general, which requires specific pelvic exercise.